2016
DOI: 10.1177/0033688216631177
|View full text |Cite
|
Sign up to set email alerts
|

Unpacking in-service EFL Teachers’ Critical Incidents: The Case of Iran

Abstract: Despite the importance of reflection on critical incidents (CIs), there are only a few studies in ELT literature addressing English language teachers' CIs (Farrell, 2008). Accordingly, this study was conducted to explore and discuss how six in-service EFL teachers reflected on and reported their CIs. In so doing, the participant teachers reflected retrospectively and introspectively on their CIs for 12 sessions. They put their CIs in a blog each session in order to share them with their colleagues. After the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 22 publications
1
12
0
Order By: Relevance
“…As a teacher, it’s hard to keep them all fully satisfied, although we must do our best to do so. (taken from Atai & Nejadghanbar, 2016)…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…As a teacher, it’s hard to keep them all fully satisfied, although we must do our best to do so. (taken from Atai & Nejadghanbar, 2016)…”
Section: Resultsmentioning
confidence: 99%
“…The results of their study led to the emergence of six categories with 12 subcategories of CIs as shown in Figure 1. The rationale for the choice of CIs was based on Atai and Nejadghanbar (2016, 2017), who argue for systematic inclusion of CIs in English teacher education programs. They suggest that in order to use CIs in teacher education programs, CIs should be selected based on their frequency of occurrence in the contexts in which the teachers will teach.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations